Evaluating the Site of Avrocity as a High-Rise Residential Project in Duhok City According to LEED Sustainable Rating Criteria - Dhuoki, Riman; Çağnan, Çiğdem (European Journal of Sustainable Development, 2021)
Duhok city faced many challenges in the last decades because of urban and population growth especially in the residential sector because there is shortage in providing housing units annually. High-rise residential projects are one of the common solutions to overcome the deficit. Yet, these kinds of residential projects have many issues since it is a new method of development within the city. From here the main aim of this study come to light which is to improve the quality of high-rise residential projects site in accordance to sustainable rating system and establish effective regulations framework with the help of internationally accepted criteria. The reason for upgrading the regulations is that the sites of these projects do not offer healthy built environment to their residents. The lack of nearby social and technical infrastructures caused more distances to be covered by vehicles resulting environmental pollution which could cause global warming. To investigate and evaluate the high-rise residential projects site according to Leadership in Energy and Environmental Design (LEED) sustainable rating tool, a residential project site has been chosen, which is; Avrocity project. The information had been analyzed qualitatively. The obtained results demonstrated that, the lack of updated regulations in Duhok city lead to improper planning and deficiency of services within residential projects site.